Preparation of polycaprolactone/ethanolic extract propolis nanofibers films - Sutjarittangtham K. (2014)
Recent years, propolis has plenty of biological and pharmacological properties and its mechanisms of action have been widely investigated. There is a substantive database on the biological activity and toxicity of propolis indicating it may have many antibiotic, antifungal, antiviral and antitumor properties, among other attributes. The one-step incorporation of propolis into nanofibrous mats of polycaprolactone (PCL) by electrospinning was demonstrated. In this research, the preparation of the PCL nanofibers films added ethanolic extract propolis (EEP) by electrospinning technique was studied. The EEP content was varied from 0, 2, 4, 6, 8 and 10%. The morphology was observed by a scanning electron microscope (SEM). The functional group was investigated by FT-IR. © (2012) Trans Tech Publications.